(untitled) - Ravindran, A. (Hoboken, N.J., 2006)
Engineering optimization helps engineers zero in on the most effective, efficient solutions to problems. This text provides a practical, real-world understanding of engineering optimization. Rather than belaboring underlying proofs and mathematical derivations, it emphasizes optimization methodology, focusing on techniques and stratagems relevant to engineering applications in design, operations, and analysis.
Keywords: Engineering,Mathematical optimization; Mathematical models; Tối ư hóa (Toán học),Kỹ thuật; Mô hình toán học